Drought Diagnosis: What the Medical Sciences Can Teach Us. Issue 4 (2nd April 2022) - Walker, David W.; Cavalcante, Louise; Kchouk, Sarra; Ribeiro Neto, Germano G.; Dewulf, Art; Gondim, Rubens S.; Martins, Eduardo S. Passos Rodrigues; Melsen, Lieke A.; de Souza Filho, Francisco de Assis; Vergopolan, Noemi; Van Oel, Pieter R.
Abstract: Drought management is currently informed by a variety of approaches, mostly responding to drought crisis when it happens. Toward more effective and integrated drought management, we introduce a conceptual drought diagnosis framework inspired by diagnostic concepts from the field of medicine. This framework comprises five steps: 1. Initial diagnostic assessment; 2. Diagnostic testing; 3. Consultation; 4. Communication of the diagnosis; and 5. Treatment and prognosis. To illustrate the need for the proposed approach, four case studies of recently drought‐affected regions were selected: the city of Cape Town, the state of California, the Northeast region of Brazil, and the Horn of Africa. Contrasting elements for these cases include the geographic extent and political boundaries, climate, socio‐economics, and the relevance of different water resources (e.g., rainfall, reservoirs, and aquifers). For each case, we identified documented practices and policies and reflected on them in terms of drought misdiagnosis or incomplete diagnosis that have aggravated socio‐economic and environmental drought impacts. A common example is the preference for technical solutions (e.g., installing infrastructure to augment water supply), rather than measures that reduce vulnerability. Analysis of these four drought case studies confirmed the anticipated need for a comprehensive approach to drought diagnosis for more successful treatment and prevention of drought. Using an analogy with medical science can be helpful toward comprehensively diagnosing droughts for a variety of contexts and assessing the effectiveness of proposed interventions. This framework can help drought managers to be more proactive in enabling drought‐affected regions to become more drought resilient in the future. Plain Language Summary: Droughts are becoming more common around the world, are occurring in new areas, lasting longer, and are affecting more people. When drought hits, we often experience water shortages, which can affect agriculture leading to food shortages. Additional drought impacts on health, lifestyle, and ecosystems include drying rivers and lakes, dust storms, water use restrictions, a lack of snow, dying forests, and wildfires. In extreme cases, droughts cause famine, disease, and migration. The fact that such drought impacts regularly make the news shows how ineffectively we currently manage drought; because the common practice is to respond to drought crisis as it happens rather than preparing in advance. Considering drought as a health disorder, we can follow the process used in medicine to diagnose that disorder and prescribe treatment. We suggest using this approach would enable us to identify where and how a location is vulnerable to drought and work on treatments. We could improve the health of a location before drought hits, thus reducing drought impacts. We discuss four recent drought cases: the city of Cape Town, state of California, Northeast region of Brazil, and Horn of Africa, to illustrate how drought could be better dealt with using our proposed approach. Key Points: Analysis of recent droughts shows that drought diagnosis is often insufficient leading to unsuccessful strategies to deal with drought Drought diagnosis can be improved by using an analogy with the medical diagnostic process This emphasizes that the focus of a comprehensive drought diagnosis should be to prescribe treatment that reduces drought impacts